Lower gastrointestinal function after surgery for deep endometriosis: A prospective cohort study. Issue 1 (8th August 2022) - Dior, Uri P.; Reddington, Charlotte; Cheng, Claudia; Levin, Gabriel; McInerney, Carmel; Moss, Alan; Healey, Martin
Abstract: Objective: To prospectively compare long‐term lower gastrointestinal function before and after laparoscopic surgery for deep endometriosis (DE). Methods: In this prospective observational study we followed 149 patients with confirmed DE who were treated surgically. Patients completed the International Consultation on Incontinence Questionnaire Anal Incontinence Symptoms and Quality of Life Module (ICIQ‐B) before surgery, and 6 weeks, 6 months, and 12 months after surgery. Bowel pattern, bowel control, and bowel impact on quality of life summary scores were compared before and after surgery. Results: Bowel pattern score showed an increasing improvement at all time points after surgery, from a mean pre‐operation score of 4.8 ± 2.0 to 4.4 ± 1.8 at 6 weeks, 4.2 ± 1.8 at 6 months, and 4.2 ± 1.2 at 12 months. Bowel impact on quality of life significantly improved from pre‐surgery mean score of 5.5 ± 6.0 to 4.2 ± 5.5 at 6 weeks and 4.4 ± 5.4 at 6 months. Direct lower gastrointestinal endometriosis involvement and worse initial function were associated with larger improvements in scores following surgery. Conclusions: Lower gastrointestinal function significantly improved after surgical treatment of DE. Further research is needed to confirm our findings and to better characterize the sub‐groups of patients for whom surgery will have a beneficial effect on their bowel function. Synopsis: Bowel pattern and bowel quality of life improved after surgery for deep endometriosis. Initial worse function was associated with greater functional improvement.